(untitled) (Research, Society and Development, 2021)
This work analyzed the context of formation of an important business incubator in the Brazilian Midwest, the Active Incubator of the Federal Institute of Mato Grosso – IFMT. Its objective was to understand how the training offered by the IFMT’s Active Incubator contributes to overcoming situations of vulnerability evidenced in the initial diagnosis of the incubator. The researched public were the Ativa’s own incubators in 2021. The methodology was qualitative and the method a case study. The methodological procedures were based on three stages inherent to the developed incubation: 1) disclosure of vulnerabilities from the diagnosis made with the incubated, 2) disclosure of the training stages offered by the IFMT Incubator Active through the Entrepreneurial Skills Course, and 3 ) possibilities of training to overcome vulnerabilities. The analysis also took place in stages: 1) confrontation between the most frequently found vulnerabilities and the concepts offered in training capable of supporting this overcoming; and 2) analysis of training based on educational assumptions that theoretically structure the practical training – a characteristic of the entrepreneurial skills course of the Active Incubator at IFMT. The analyzes and data showed that the contribution of the training offered by Ativa is doubly guided towards overcoming vulnerabilities, since on the one hand it has a structured curriculum with concepts capable of confronting the vulnerabilities of its incubated companies, and on the other hand it practices follow-ups that analyze the application practice of the training offered, offering solutions through direct assistance and consultancy.